2014
DOI: 10.5230/jgc.2014.14.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Serial Comparisons of Quality of Life after Distal Subtotal or Total Gastrectomy: What Are the Rational Approaches for Quality of Life Management?

Abstract: PurposeThe aims of this study were to make serial comparisons of the quality of life (QoL) between patients who underwent total gastrectomy and those who underwent distal subtotal gastrectomy for gastric cancer and to identify the affected scales with consistency.Materials and MethodsQoL data of 275 patients who were admitted for surgery between September 2008 and June 2011 and who underwent subtotal gastrectomy or total gastrectomy were obtained preoperatively and postoperatively at 3, 6, 9, 12, 18, and 24 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 25 publications
4
46
0
Order By: Relevance
“…Date regarding to patient 30-day mortality at postoperation were reported in eight studies[6,7,9,1113,15,16] involving 1866 patients of TG and 2424 patients of DG. The accumulated mortality rates of TG and DG groups were 2.14% (40/1866) and 1.16% (28/2424) respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Date regarding to patient 30-day mortality at postoperation were reported in eight studies[6,7,9,1113,15,16] involving 1866 patients of TG and 2424 patients of DG. The accumulated mortality rates of TG and DG groups were 2.14% (40/1866) and 1.16% (28/2424) respectively.…”
Section: Resultsmentioning
confidence: 99%
“…With the improvement of surgical techniques and the development of the instruments, the number of long-term survivors after resection for gastric cancer has been increasing and their QoL has become an important issue. In this study, due to lacking of QoL questionnaire standard scales, several articles we searched in comparison to short- or long-term QoL after undergone TG and DG could not be system evaluated[16,27,31–36]. Studies have shown that patients who undergone DG have a better QoL than those who undergone TG in shroter postoperative follow-up period[36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical features of PGS include the occurrence of various symptoms, reduced dietary intake, weight loss, reduced physical activity, and reduced physical and mental QOL. PGS is usually the most severe after TG, and the postoperative QOL of patients is known to be better after DG, in which the proximal stomach is partially preserved, than after TG[8,10,13,18,19]. Our study also showed a significantly higher “necessity for additional meals”, greater “weight loss”, lower “ability for working” and worse “dissatisfaction for daily life SS”, “PCS” and “MCS” of SF-8 in the TG group than in the DG group.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported a greater deterioration of the QOL after total gastrectomy (TG) than distal gastrectomy (DG)[8,10,13,18,19], and it is thought that the more extensive the resection of the stomach, the greater the severity of PGS[11]. On the other hand, function-preserving gastrectomy, in which the extent of gastrectomy is reduced, such as pylorus-preserving gastrectomy (PPG)[9,11,16,17,23] and proximal gastrectomy[20], is often used for treating early gastric cancer and has been reported to be useful to improve the QOL of patients after surgery.…”
Section: Introductionmentioning
confidence: 99%